Local density of states in a dirty normal metal connected to a superconductor - Belzig, Wolfgang; Bruder, Christoph; Schön, Gerd (My University, 1998)
A superconductor in contact with a normal metal not only induces superconducting correlations, known as the proximity effect, but also modifies the density of states at some distance from the interface. These modifications can be resolved experimentally in microstructured systems. We therefore study the local density of states N(E,x) of a superconductor normal-metal heterostructure. We find a suppression of N(E,x) at small energies, which persists to large distances. If the normal metal forms a thin layer of thickness Ln , a minigap in the density of states appears which is of the order of the Thouless energy ~ħD/Ln². A magnetic field suppresses the features. We find good agreement with recent experiments of Guéron et al.
Keywords: 530